2001
DOI: 10.1007/s002320010051
|View full text |Cite
|
Sign up to set email alerts
|

Ion Selectivity of the Cytoplasmic Binding Sites of the Na,K-ATPase: II. Competition of Various Cations

Abstract: Abstract.In the E 1 state of the Na,K-ATPase all cations present in the cytoplasm compete for the ion binding sites. The mutual effects of mono-, di-and trivalent cations were investigated by experiments with the electrochromic fluorescent dye RH421. Three sites with significantly different properties could be identified. The most unspecific binding site is able to bind all cations, independent of their valence and size. The large organic cation Br 2 -Titu 3+ is bound with the highest affinity (< M), among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 35 publications
5
66
2
1
Order By: Relevance
“…The results of the crystal structure of the SR Ca-ATPase (Toyoshima et al, 2000), which revealed the position of the Ca 2+ binding sites in the middle of the membrane, and of the electrogenicity of all ion-binding steps, Ca 2+ and H + ions (Butscher et al, 1999, Peinelt & Apell, 2002, as well as the similar¯uorescence responses of all nXITC dyes on the investigated partial reactions as shown in this paper, ®t well together. This structural concept of ion-binding sites that are located in the center of the membrane, is in strong contrast to the observations made with the Na,K-ATPase so far: On the cytoplasmic side, binding of only the third Na + ion is electrogenic, i.e., within the protein dielectric; all other ions, be that Na or K , have to bind close to the surface or in wide, water-®lled vestibules that are still part of the dielectric protein surface (Goldshlegger et al, 1987, Bahinski et al, 1988, Rakowski et al, 1990, Domaszewicz & Apell, 1999, Schneeberger & Apell, 2001). In the experiments presented it could be shown unambiguously that various dyes respond di erently on electrogenic Na + binding, which is a strong indication that an ion is being bound within the sensitive length of the styryl chromophores and not in the center of the membrane.…”
Section: Structure-function Relations Deduced From the Experimental Ocontrasting
confidence: 73%
See 1 more Smart Citation
“…The results of the crystal structure of the SR Ca-ATPase (Toyoshima et al, 2000), which revealed the position of the Ca 2+ binding sites in the middle of the membrane, and of the electrogenicity of all ion-binding steps, Ca 2+ and H + ions (Butscher et al, 1999, Peinelt & Apell, 2002, as well as the similar¯uorescence responses of all nXITC dyes on the investigated partial reactions as shown in this paper, ®t well together. This structural concept of ion-binding sites that are located in the center of the membrane, is in strong contrast to the observations made with the Na,K-ATPase so far: On the cytoplasmic side, binding of only the third Na + ion is electrogenic, i.e., within the protein dielectric; all other ions, be that Na or K , have to bind close to the surface or in wide, water-®lled vestibules that are still part of the dielectric protein surface (Goldshlegger et al, 1987, Bahinski et al, 1988, Rakowski et al, 1990, Domaszewicz & Apell, 1999, Schneeberger & Apell, 2001). In the experiments presented it could be shown unambiguously that various dyes respond di erently on electrogenic Na + binding, which is a strong indication that an ion is being bound within the sensitive length of the styryl chromophores and not in the center of the membrane.…”
Section: Structure-function Relations Deduced From the Experimental Ocontrasting
confidence: 73%
“…If, in contrast, the dye molecules are di using through the lipid phase of the membrane, an increase of the dye concentration would hardly a ect the amplitude of DF/F 0 because the (average) electric ®eld in the membrane is not signi®cantly altered when the ratio of 60 lipids per dye molecule is decreased to 20. On the other hand, it was shown that partial reactions, which contain con-formational transitions but no change of the number of ions inside the protein, did not a ect the¯uores-cence emission, such as E 1 + 2K + ® E 2 (K 2 ) (StuÈ rmer et al, 1991;BuÈ hler & Apell, 1995;Schneeberger & Apell, 2001) or Na 3 E 1 ® P-E 2 Na 3 , which can be observed in high Na + concentrations (StuÈ rmer & Apell, 1992;Heyse et al, 1994). In the case of 2BITC and 2HITC, conformational transitions of the SR Ca-ATPase were also not accompanied by signi®cant uorescence changes (Butscher et al, 1999, Peinelt & Apell, 2002.…”
Section: Detection Mechanism Of the Styryl Dyesmentioning
confidence: 99%
“…No other ion but Na + was found to bind to the third ion binding site, and the affinity for Na + binding to the third ion binding site is higher than for the second (Schneeberger & Apell, 2001). From these findings it was concluded that the third ion binding site becomes available only after the first two sites are occupied.…”
Section: Discussionmentioning
confidence: 67%
“…9, box III). Binding constants for the Na + ions in absence of MCS factors and at pH 7.0-7.2 were already established before (Schulz & Apell, 1995, Schneeberger & Apell, 2001, and are adopted for this simulation as KNa1 = 1 lM, KNa2 = 0.8 mM, and KNa3 = 0.9 lM. The simulations carried out with this model could not match the experimental data nor even appropriately represent the trends in fluorescence increases as observed in the experiments (not shown), similar to the respective approach described above for the K + and H + pathway.…”
Section: Na + Pathwaymentioning
confidence: 99%
“…Previously published careful equilibrium titrations have shown in fact that the fluorescence decrease is due to the binding of the third Na + ion to the E 1 conformation, that is, the formation of the E 1 (Na + ) 3 state (39,40). The binding of the first and second Na + ions do not produce any fluorescence change.…”
Section: Discussionmentioning
confidence: 87%